The problems of Google Translate: Los servicios de la traducción automática de Google y sus problemas (Journal of the College of Languages (JCL), 2021)
There are numbers of automatic translation services that internet users can choose to automatically translate a certain text, and Google translate is one of these automatic services that proposes over 51 Languages. The present paper sheds light on the nature of the translation process offered by Google, and analyze the most prominent problems faced when Google translate is used. Direct translation is common with Google Translate and often results in nonsensical literal translations, particularly with long compound sentences. This is due to the fact that Google translation system uses a method based on language pair frequency that does not take into account grammatical rules which, in turn, affects the quality of the translation. The complexity of the text, as well as any context which cannot be interpreted without a true knowledge of the language, makes the likelihood of errors greater. Professional translators take great pains to ensure that this does not happen by using well-established online glossaries, back translation methods, proof readers and reviewers. The present paper discusses the Google translate of advertisements, Al-Qur’an holy texts as well as literary texts out of Arabic into Spanish stressing the pros and cons of Google translate that not only impact professional translators in the language service industry but also take the interest of the language experts. Existen varios servicios de la traducción automática que los usuarios del internet pueden elegir entre varios con el fin depoder traducir automáticamente un determinado texto, uno de estos servicios de la traducción automática es elGoogle que es uno de los servicios más popularesque permite traducir los textos a 51 idiomas. El presente trabajo de investigación tiene como objetivo explorar la naturaleza del proceso de la traducción dada por el servicio de traducción de Google, analizando los problemas más destacados que surjan a la hora de traducir, ya que el traductorque usa el Google es, de ninguna manera, un traductor profesional, y por lo tanto, puede llegar a una traducción totalmente catastrófica.